2022
DOI: 10.3389/fneur.2022.875134
|View full text |Cite
|
Sign up to set email alerts
|

Non-HDL-C/HDL-C ratio is associated with carotid plaque stability in general population: A cross-sectional study

Abstract: and Wang L ( ) Non-HDL-C/HDL-C ratio is associated with carotid plaque stability in general population: A cross-sectional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
0
17
1
Order By: Relevance
“…Recently, there has been a growing interest in the role of other atherogenic lipoproteins in the development of atherosclerosis and its associated clinical outcomes 21–23 . A study involving 27 436 urban workers in China found a significant association between the non‐HDL‐C/HDL‐C ratio and the stability of carotid plaque 24 . Likewise, a study of 426 patients with first‐onset non‐ST‐segment elevation acute myocardial infarction (NSTEMI) indicated that the non‐HDL‐C/HDL‐C ratio is significantly associated with severe coronary lesions and functions as an independent predictor of cardiovascular outcomes among NSTEMI patients 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been a growing interest in the role of other atherogenic lipoproteins in the development of atherosclerosis and its associated clinical outcomes 21–23 . A study involving 27 436 urban workers in China found a significant association between the non‐HDL‐C/HDL‐C ratio and the stability of carotid plaque 24 . Likewise, a study of 426 patients with first‐onset non‐ST‐segment elevation acute myocardial infarction (NSTEMI) indicated that the non‐HDL‐C/HDL‐C ratio is significantly associated with severe coronary lesions and functions as an independent predictor of cardiovascular outcomes among NSTEMI patients 25 .…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 , 23 A study involving 27 436 urban workers in China found a significant association between the non‐HDL‐C/HDL‐C ratio and the stability of carotid plaque. 24 Likewise, a study of 426 patients with first‐onset non‐ST‐segment elevation acute myocardial infarction (NSTEMI) indicated that the non‐HDL‐C/HDL‐C ratio is significantly associated with severe coronary lesions and functions as an independent predictor of cardiovascular outcomes among NSTEMI patients. 25 Furthermore, an analysis of 46 786 patients with type 2 diabetes showed that lower levels of non‐HDL‐C/HDL‐C are more effective risk markers for ASCVD compared to LDL‐C levels below 3 mmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation was found to be particularly significant among women ( 13 ). Additionally, a study based on an urban Chinese cohort revealed that the non-HDL-C/HDL-C ratio was notably linked with the stability of carotid plaques, suggesting that it could serve as a valuable marker for the early detection of carotid plaques at elevated risk ( 47 ). Given that carotid atherosclerosis plays a significant role in stroke development ( 48 ), it is noteworthy that a recent Chinese cohort study discovered a positive association between the non-HDL-c/HDL-c ratio and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…As a signi cant lipid marker for plaque prevention as well as a novel risk factor for the development of atherosclerotic plaque, NHHR is considered an emerging lipid biomarker for atherosclerosis [11,29].…”
Section: Discussionmentioning
confidence: 99%
“…The focus of this study was on NHHR, which was identi ed as the key variable. Calculation of NHHR employed methodologies derived from previous research [11]. Total cholesterol (TC) and HDL cholesterol (HDL-C) levels were evaluated using enzymatic assays conducted on automated biochemistry analyzers [12].…”
Section: Exposure De Nitionmentioning
confidence: 99%